Designing Rt/Rw Net In Implementing Load Balancing Using Per-Connection Classifier Method In Bumi Mas Housing - Saputra, Febri Wangsa; Aspriyono, Hari; Akbar , Abdussalam Al (CV. Generasi Insan Rafflesia, 2022)
The need for the internet during the current COVID-19 pandemic is very high, because students, college students, office employees and others have to do all activities at home. This causes increase in connection traffic on the internet and workloads on internet service provider servers. RT/RW-Net is a concept where several computers in a housing or block can be interconnected and can share data and information. To solve this problem, a load balancing technique is applied, namely load distribution and setting the client connection path to a service that is on the server by utilizing the connection distribution method using the PCC (Per-Connection Classifier) method. The result of this research is it has succeeded in designing RT/RW-Net in Bumi Mas Housing by implementing Load Balancing using the Per-Connection Classifier (PCC) method. In implementing Load Balancing and Per-Connection Classifier (PCC) it can solve the problem when one of the ISPs is interrupted or the internet network is disconnected, the connection will automatically be transferred to an active ISP. So that network performance continues to run normally and also with load balancing with the PCC method it doesn't burden traffic and actually divides the load.